INTEGRATION OF SHARIA MAQASHID AND ISLAMIC WORK-LIFE BALANCE: SUSTAINABLE EMPLOYEE WELL-BEING FRAMEWORK IN SHARIA FINANCIAL INSTITUTIONS (SLR) - Yori Kurniawati; Fadhila Husna; Syerly Lia Azharah; Sandra Dewi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
Sharia Financial Institutions (LKS) bear a dual responsibility: achieving financial performance while ensuring Sustainable Employee Welfare (SEWB) is aligned with the mission of maslahah. Contemporary Human Resource Management (SDI) practices often fail to integrate the spiritual dimension, which triggers problems such as burnout and turnover intention. This study aims to synthesize the SEWB strategic model in LKS through a Systematic Literature Review (SLR), in order to bridge the normative gap and operational implementation of SDI. The SLR method was carried out by analyzing the latest literature (2020–2025) on Maqashid Sharia, Islamic Work-Life Balance (I-WLB), and SEWB. The results of the synthesis formulate a causal model: a sustainable SEWB (falah) is achieved through integration. The Sharia Maqashid serves as a philosophical foundation and ethical compass, while the I-WLB acts as an operational strategic mechanism. Specifically, Hifz al-Nafs and Hifz al-Aql are operationalized through the I-WLB policy for the mental and spiritual protection of employees. This model implies the need for Islamic Financial Institutions to develop a Human Resources policy based on three main pillars: spiritual, personal, and social, which is ready to be empirically tested.